PENGARUH PENDIDIKAN MENGGUNAKAN MEDIA BOOKLET TERHADAP PENGETAHUAN PENCEGAHAN COVID-19 PADA SISWA SDN 41 & SDN 82 KOTA BENGKULU - Mardiyaningsi, Riris; Husni, Husni; Sahran, Sahran; Asmawati, Asmawati; Annisa, Rahma (LPPM STIKES BHAKTI HUSADA BENGKULU, 2022)
ABSTRACTIntroduction : Coronavirus Disease is a virus that infects the respiratory system, the corona virus was first discovered in Wuhan, China at the end of 2019 called Covid-19. Transmission of Covid-19 can be spread through the saliva splashes (droplets) that a person releases when coughing, sneezing, or even talking. Droplets can fall and stick to nearby objects, therefore, hands holding objects that are splashed with saliva become a place for transmission of Covid-19 transmission when touching the nose, mouth and eyes. The program that has been carried out by the Government of Indonesia with health protocols by washing hands, maintaining distance, using masks, consuming healthy food and exercising to reduce the spread of Covid-19. Methods:This study was conducted to identify the knowledge of elementary school students at SDN 41 & 82 Bengkulu City on the prevention of Covid-19 by using booklets. The design of this study was a quasi-experimental with pre-post design with a control group. The research sample was 50 people consisting of 25 people in the control group and 25 people in the intervention group. The sampling technique used is random sampling. Analysis using t test Results:the results showed that the average knowledge before intervention in the intervention group was 61.60 and in the control group 60.40 after the intervention was carried out the average knowledge in the intervention group was 83.60 and in the control group was 66.00. Conclusion: The results of the analysis show that there is a difference in the average knowledge of p value of 0.000. Educate knowledge on prevention of Covid-19 using booklets.Keywords: Covid-19 Prevention, Knowledge, BookletABSTRAKPendahuluan : Coronavirus Disease adalah virus yang menginfeksikan sistem pernafasan corona virus pertama kali ditemukan Wuhan China pada akhir tahun 2019 disebut dengan Covid-19. Penularan Covid-19 dapat menyebar melalui cipratan liur (droplet) yang dikeluarkan seseorang ketika barsin, batuk, bahkan saat bicara. Droplet dapat jatuh dan menempel pada benda disekitar oleh karena itu, tanggan yang memegang benda yang terciprat liur menjadi tempat transmisi penularan Covid-19 ketika menyentuh hidung, mulut dan mata. Program yang sudah dilakukan oleh Pemerintah Idonesia dengan protokol kesehatan dengan mencuci tanggan, menjaga jarak, mengunakan masker, mengkonsumsi makan yang bergizi dan berolahraga guna mengurangi penyebaran Covid-19. Penelitian ini dilakukan untuk mengidentifikasi pengetahuan siswa sekolah dasar di SDN 41 & 82 Kota Bengkulu terhadap pencegahan Covid-19 dengan mengunakan booklet. Metode : Desain penelitian ini adalah quasi experiment dengan pre-post desing with control grup. Sampel penelitian berjumlah 50 orang yang terdiri 25 orang pada kelompok kontrol dan 25 orang pada kelompok intervensi. Tehnik sampling yang digunakan adalah random sampling. Analisi menggunakan t test Hasil : hasil menunjukan bahwa rata-rata pengetahuan sebelum diakukan intervensi pada kelompok intervensi 61,60 dan pada kelompok kontrol 60,40 setelah intervensi dilakukan rata rata pengetahuan pada kelompok intervensi 83,60 dan pada kelompok kontrol 66,00. Simpulan :Hasil analisi menunjukan adanya Perbedaan rata-rataPengetahuanp value 0,000. Edukasi Pengetahuan Pencegahan Covid-19 mengunakan booklet. Kata Kunci : Pencegahan Covid-19, Pengetahuan, Boklet